FoodSupportNearYou - Yee, Shao JIe (Nanyang Technological University, 2022)
FoodSupportNearMe, is a mobile application that is designed in the context of Singapore and aims to provide food assistance to everyone and anyone by engaging the whole of Singapore community to come together to fight against food insecurity. FoodSupportNearMe is developed through a process of understanding the problem, empathising with people who face food insecurity, understanding stakeholders through organisational needs and understanding the mindsets of potential users.